Reinforced concrete by using the rectangular shape of voided beam - Idris, Nur’Ain; Mohd Noh, Hamidun; Mohamad, Nor Lailatul Izzatil Azwani; Bangau, Rolly (Universiti Teknologi MARA (UiTM), Malaysia, 2020)
In conventional RC beam, the transition from compression to tension zone of the beam when load applied producing ineffective region at the middle area of the neutral axis. This is because, the area experiencing less compression and tension compare to the region above and below the neutral axis. Thus, the purpose of this research is to replace the use of concrete at the middle of the neutral axis by incorporating 4 PVC pipes to reduce cost and the self-weight of the structure. 4 pipes with a diameter of 20mm, 25mm and 50mm will be combined together to form a continuous voided square beam of V40, V50 and V100. The size of RC beam specimens is 1200mm x 160mm x 160mm, these beams were test with 3-point load test to identify the flexural strength. From the test, the ordinary beam recorded lowest maximum load, which is 15,35kN and VRB 100mm is the strongest beam with the maximum load 33.75kN and has the highest strength increment compared to another voided rectangular beam. Besides that, VRB 100mm also can reduced until 42.69% self-weight of RC beam and reduce until 37.5% of the concrete usage. From this study, it shows that the Voided Square Beam can reduce the self-weight of beam and reduce the concrete usage. Besides that, this idea also can implement to produce the lightweight structure that meet the standard of Industrialized Building System (IBS).